Risk factors for cesarean surgical site infections at a Thai-Myanmar border hospital - Srisuda Assawapalanggool (2018)
© 2016 Association for Professionals in Infection Control and Epidemiology, Inc. Background Cesarean surgical site infections (SSIs) are a major challenge in Thai-Myanmar border hospital settings. This study aimed to examine risk factors for SSIs after cesarean section. Methods This was a prospective cohort study conducted in a Thai-Myanmar border hospital between January 2007 and December 2012. Data were collected from the medical record database by trained infection control nurses. Stepwise multivariable logistic regression was used for risk factor analysis and expressed as a risk ratio (RR). Results The cesarean SSI rate was 5.9% (293 SSIs in 4,988 cases). Of these, 17.1% were incisional SSIs (10.9% superficial and 6.2% deep incisional SSIs), and 82.9% were organ or space SSIs. Risk factors for cesarean organ-space SSIs included a wound class ≥3 (RR, 4.82; 95% confidence interval [CI], 3.41-6.83), ethnic minority (RR, 2.51; 95% CI, 1.61-3.92), hemoglobin <11 g/dL (RR, 2.19; 95% CI, 1.57-3.04), pelvic examination before delivery on ≥5 occasions (RR, 4.16; 95% CI, 2.89-5.99), preterm (RR, 1.98; 95% CI, 1.33-2.95), being a local referral (RR, 3.37; 95% CI, 2.29-4.97), and foul-smelling amniotic fluid (RR, 21.08; 95% CI, 10.23-43.41). Conclusions Most cesarean SSIs in this study seem to have a high severity. Their risk factors reflected delayed appropriate perinatal maternal care that resulted in late cesarean delivery. Early prenatal care may help reduce cesarean SSIs among this population.